Assaults on police officers: A comparison between England and Wales and New Zealand from 2015 to 2022 - Heyer, Garth den (International journal of police science & management, 2024)
This research discussed in this article examined assaults on police officers in England and Wales and in New Zealand between 2015 and 2022. Although different sources of data were used to examine the number of assaults on police officers in the three countries, it was found that the number of assaults on police officers in England and Wales and in New Zealand increased during this period. England and Wales experienced a 56% increase in the number of assaults on police officers, while the New Zealand Police experienced a 41% increase. Using the population of each country as a basis there was an increase in the number of assaults of more than 16% in New Zealand and more than 63% in England and Wales. The main limitation of the research was that the information that was available lacked detail, and this would limit the development of policy to minimize the threat to police officers of being assaulted.